Relationship between digital development and subjective well-being in chilean school children. (January 2021) - Donoso, Gonzalo; Casas, Ferran; Oyanedel, Juan Carlos; López, Mauricio
Abstract: This study explores how access, management and use of Information and Communication Technologies in secondary schools are related to the subjective well-being of adolescents. The central hypothesis of this work is that students attending schools with high digital development have higher levels of subjective well-being. To test this hypothesis, two quantitative empirical studies carried out in Chile are used as sources of information. The first one is the 2013 National Survey of School Well-being, applied to 15-year-old students (4964 cases) from 191 schools, and the second one is the 2012 National Census of Educational Computing. Subsequently, after both sources are merged, a descriptive analysis and an explanatory model are created based on the dependent variable Personal Wellbeing Index (PWI), and the independent variables School Digital Development Index (SDDI) and attributes of establishment and subjects. Among the results, the finding of a positive and significant relationship between school digital development and higher subjective well-being scores of students stands out. Highlights: The subjective well-being of students is directly associated to school climate. Digital development in schools has a positive relation with well-being in children. Students' subjective well-being is higher in schools with higher ICT development. Educational use of ICT is associated with higher subjective well-being of students.